The Legal Order And İts Relation With The Power And The Economy İn The Current Brazilian Scenery, İnstrumentality a priori And Rationality a posteriori - Bruno Augusto Sampaio Fuga (European Scientific Journal, ESJ, 2016)
The Brazilian Legal system and its relation with the power in the current Brazilian scenery, and also the use of a posteriori rationality of the judge and the priori instrumentality of the legislator and of the Executive, is the theme of the present study. Its goal is to show a brief historical evolution of the Law and the State, the Power aspects, the forms of State and its acting with the origin of population. The next step is to present the use of Brazilian Legal System as a form of organization, that is, a priori instrumentality and the evolution from Liberal State to Social State, with significant changes in the legal aspects and in its form of acting. Furthermore, we carry on with the world crisis, especially the one of 1929, whose changes imposed by the end of Second World War (the decline of legal positivism) and also the advances which came with the globalization in 1990. Still considering crisis, it is discussed about the 2008 crisis and its consequences, the European crisis with its high costs of a Social State. A parallelism was done between the economy and the Law and besides that, it was drawn a legal scenery after these evolutions. Regarding these relations of power and the crisis of the power tripartism, we also showed that an ascension of Legal Law can be named as the legal protagonist or, for some, legal activism. These role has some reflexes in the Judicial Discretion, in the active management of processes, in the legal inflation of the Legislative and Executive (provisional measures), in the use of process as a strategy of power, in the legalization of politics and in the creation of binding overviews. Some case studies and considerations about justice were showed. This research is justified because the power, the contemporary legal scenery, the judicial role, the economy and the Law, and the forms of acting of the State (Liberal and Social) are current themes in the study of operators and Law scholars. Thus as these inquiries show great influence in the democratic state of Law.